(untitled) (International Journal of Innovative Computing, 2024)
In a world where safety is a growing concern, sexual harassment and physical violence have become significant societal concerns. A particularly pressing need for action and reduction in the alarming number of rape cases and violence against women can be seen especially in developing countries, where rape cases and violence against women are on the rise. In order to protect themselves from potential predators and criminals, women must remain vigilant. Developed to empower women during such harrowing incidents, Fearless is a groundbreaking mobile application designed to prevent sexual harassment and physical violence. Using the Google Firebase platform, this innovative application allows users to instantly share their location with trusted contacts to startle potential attackers, share their experiences, or raise awareness. As a result of its interface design principles, Fearless has a highly manageable, user-friendly, and efficient mobile interface. In addition to its compatibility and convenience, it facilitates seamless data management by integrating with NoSQL systems. The system development plan was successfully implemented using the agile process after rigorous comparisons with existing and proposed systems. Fearless emerged as the ideal solution, shaping the entire architectural design. In order to ensure the application’s reliability and effectiveness, post-development testing, including black box testing and user acceptance testing, was conducted.